Indie Writers’ Thoughts On Malaysia’s Political Reality: Lukacs’ Realism Analysis - Asyraff, Jamin; Mary Fatimah, Subet (UMK Press., 2025)
Abstract The study of realism has now received a lot of interest after being rejected and marginalised for a while by literary activities in this country. As a trend that is still in its developing phase in this country, there are still not many studies conducted using this theory in total found in Malaysia. Therefore, this study is presented to fill this existing gap, as well as to measure the enrichment of the literary studies corpus in this country. This study examines the thoughts of Indie writers on the Malaysian political situation, which was analysed from four selected Indie novels, namely Aku Rindu 90’s (2012), Surat-Surat Untuk Kaherah (2013), Kunang Pesisir Morten (2015) and Budak Kelas Belakang (2018). This study was conducted using Lukacs’ Realism criticism framework (1963, 1978, 1989, 1990) with three objectives as targets are to identify the existence of Indie writers’ thoughts towards improving Malaysia’s political situation, to present the impact of Indie writers’ thoughts on Malaysia’s political situation and lastly to rectify the community’s negative perception towards Indie works. This study eventually succeeded in identifying Indie writers’ thoughts that have an impact towards improving Malaysia’s political situation, which can be used as evidence to change the community’s negative perception of Indie works.Keywords: Indie works, Lukacs’ Realism criticism, Malaysia’s political situation, negative perception, study of realism.